Hubungan antara Perhatian Orang Tua dan Intensitas Penggunaan Smartphone dengan Hasil Belajar Ekonomi pada Peserta Didik Kelas XI IPS di SMAN 4 Palangkaraya - Susilawati Susilawati; Muhammad Andi Setiawan (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to find out: The relationship between parental attention and the intensity of smartphone use with economic learning outcomes. This study uses a quantitative approach with a correlational method. The population in this study amounted to 186 while the sample amounted to 125 students. The results of this study show there is a positive relationship between the attention of parents with the learning outcomes of economic students where the value of r count > r table or 0.900> 0.176, so Ho is rejected, There is a positive relationship between the intensity of smartphone use with learning outcomes, r count > r table or 0.355 > 0.176 , so Ho is rejected. There is a positive relationship between parental attention and the intensity of smartphone use with students' economic learning outcomes, r count > r table or 0.901> 0.176, so Ho is rejected. Thus it can be concluded that this study resulted in a significant relationship between parental attention and the intensity of smartphone use with the learning outcomes of economic students